Kinetics and Mechanism of Oxidation of Disubstituted Benzaldehydes by Pyridinium Chlorochromate - Abdul-Jameel, A. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of benzaldehyde and several disubstitutedbenzaldehydes by pyridiniurn chlorochromate (PCC)have been studied in binary solvent mixture of 50% (v/v) aqueousacetic acid. The reaction is first order each in [aldehyde], [PCC]and [H+]. Addition of monomer to the reaction mixture gives apolymer. Activation parameters have been computed and a suitablemechanism has been postulated.